(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Strangulation is a form of mechanical asphyxia by compression of the neck with an outside force either bya ligature or hands, in which a constricting force other than the weight of the body is directly applied.Suchdeaths are generally considered homicidal. Here we present a case of 60year old female, who got trapped inthe rice huller machine with the saree she was wearing and accidentally got strangled.